1998
DOI: 10.1046/j.1365-3040.1998.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of [35S]methionine in higher plants reveals that stimulation of the D1 reaction centre II protein turnover accompanies tolerance to heavy metal stress

Abstract: were studied in vivo and in vitro. Treatments of pea (Pisum sativum) and broad bean (Vicia faba) plants with 0·05-5 mM cadmium (CdCl 2 ) modified PSII activity with a resulting increase in electron transfer followed by an inhibition and damage to the oxygen-evolving complex. Pulsechase experiments with [35 S]methionine in vivo followed by the separation of the radiolabelled thylakoids into grana and stroma exposed regions indicated that the synthesis, degradation and assembly of the D1 protein were greatly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Some studies have also described increased D1 turnover as a physiological stress-compensating mechanism. Increased D1 turnover occurs in response to fumigation with ozone (36) or with mixtures of air pollutants (O 3 , NO 2 , and SO 2 ) (58), as well as during potassium deficiency (58), cadmium exposure (30,34), and drought (35). It has been proposed that D1 turnover acts as a general adaptive response to environmental extremes (35), which gives further support to our hypothesis of increased D1 turnover as an Irgarol tolerance mechanism.…”
Section: Vol 75 2009 Irgarol Tolerance and Psba Genes In Periphytonmentioning
confidence: 65%
“…Some studies have also described increased D1 turnover as a physiological stress-compensating mechanism. Increased D1 turnover occurs in response to fumigation with ozone (36) or with mixtures of air pollutants (O 3 , NO 2 , and SO 2 ) (58), as well as during potassium deficiency (58), cadmium exposure (30,34), and drought (35). It has been proposed that D1 turnover acts as a general adaptive response to environmental extremes (35), which gives further support to our hypothesis of increased D1 turnover as an Irgarol tolerance mechanism.…”
Section: Vol 75 2009 Irgarol Tolerance and Psba Genes In Periphytonmentioning
confidence: 65%
“…In the present study, F 0 was greater when soybeans were exposed to Cd or FLT. It has been reported that Cd can inhibit the flow of photosynthetic electrons, destroy the antennae pigments, inhibit the water-splitting complex of the oxidizing site of PSII, down-regulate PSII proteins, as well as competitively bind to the essential Ca 2+ site in PSII (Geiken et al, 1998;Mallick and Mohn, 2003;Faller et al, 2005). While mechanisms responsible for greater F 0 caused by FLT are not known, there are several possible hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…During photosynthesis, photosystem II (PSII) is essential to the regulation because it catalyzes the oxidation of water into oxygen (oxygen-evolving complex-Hill reaction) and supports electron transport (Geiken et al 1998). Chlorophyll fluorescence parameters can be used as indicators of stress affecting photochemical pathway of utilization of absorbed light energy based on chlorophyll fluorescence techniques (Branquinho et al 1997, Krause andWeis, 1991).…”
Section: Introductionmentioning
confidence: 99%